Răspunsuri

Cel mai inteligent răspuns!
2014-04-17T14:59:45+03:00
a. (-1 -2-3-.....-100)÷ (-101)=
(-1 -2-3-.....-100)=
-(1+2+3+....+100)=
-(100*101/2)=
-50*101=-5050

-5050:-101=50

b.
(-2 -4-6-..-200) ÷  (-101)=
-2(1+2+3+....+100):(-101)=

(1+2+3+....+100)=
100*101/2=50*101=5050
-2*5050:(-101)=
-10100:(-101)=100

unde nu intelegi intreaba-ma
nu stai linistit ca am inteles
ms frumos
2014-04-17T15:04:10+03:00
A.-(1+2+3+...+100)÷(-101)=-[(100·101)÷2]÷(-101)=-5050÷(-101)=50
b.-2(1+2+3+...+100)÷(-101)=-2[(100·101)÷2]÷(-101)=-10100÷(-101)=100
1 5 1